Exploring the Connection between Critical Thinking Skills and Academic Writing - Rahmat, Noor Hanim; Aripin, Norhartini; Lin, Nur Maizura; Whanchit, Wararat; Khairuddin, Zulaikha (International Journal of Asian Social Science, 2020)
Discussions on critical thinking skills among students in higher institutions of learning continues to be an important topic for discussion. These discussions revolve around the facts that students are not capable of displaying critical thinking skills abilities or researchers suggesting on ways to improve critical thinking skills among learners. Teachers often report on learners’ critical thinking (or lack of it) and how critical thinking skills influence classroom learning. Not many realize that writing and thinking are inter-related in many ways. The teaching of critical thinking skills can be embedded in the teaching of writing in the classroom. This study explores the connection between critical thinking skills and academic writing. It looks into how writing process mirrors critical thinking skills. This quantitative study is done on 207 first semester undergraduate students who signed up for academic writing course in a public university in Malaysia. Findings of this study revealed interesting implications for the teaching of writing process and critical thinking among undergraduates.